Reconnecting the city: the historic urban landscape approach and the future of urban heritage - Bandarin, Francesco; Oers, Ron van
Historic Urban Landscape is a new approach to urban heritage management, promoted by UNESCO, and currently one of the most debated issues in the international preservation community. However, few conservation practitioners have a clear understanding of what it entails, and more importantly, what it can achieve. Following the publication of The Historic Urban Landscape : Managing Heritage in an Urban Century, the approach is now further elaborated with a more practical slant and translates the notion into an operational set of management practices. In this follow-up book, the editors pull together specially commissioned chapters on best practice in urban heritage management from established professionals in the field. Drawn from a variety of disciplines related to urban management and conservation these authors present and discuss methodologies and practices to consider in the implementation of the Historic Urban Landscape approach as advocated by UNESCO. The contributors are selected from professionals who have written, argued or debated about the role of historic cities in contemporary society. As well as their chapters, there are interviews with six high-profile people from different regions of the world giving their critical reflections on the UNESCO approach in relation to their own ideas on urban heritage conservation and city management.